Optimization the Effect of Electrode Material Change on EDM Process Performance Using Taguchi Method - Aghdeab, Shukry H.; Abdulameer, Ahmed Ghazi; Abdulameer, Lujain Hussein; Mohammed, Atheer Rasim (Al-Khwarizmi Engineering Journal, 2020)
Electrical Discharge Machining (EDM) is a widespread Nontraditional Machining (NTM) processes for manufacturing of a complicated geometry or very hard metals parts that are difficult to machine by traditional machining operations. Electrical discharge machining is a material removal (MR) process characterized by using electrical discharge erosion. This paper discusses the optimal parameters of EDM on high-speed steel (HSS) AISI M2 as a workpiece using copper and brass as an electrode. The input parameters used for experimental work are current (10, 24 and 42 A), pulse on time (100, 150 and 200 µs), and pulse off time (4, 12 and 25 µs) that have effect on the material removal rate (MRR), electrode wear rate (EWR) and wear ratio (WR). A Minitab software environment was used to adopt Taguchi method to analyze the effect of input on output parameters of EDM. The results of the present work showed that the best of MRR in copper and brass electrodes with (current 42 A, pulse on time 100 µs and pulse off time 25 µs) are (84.355×10-3 g/min) and (43.243×10-3 g/min) respectively, and the MRR predicted by Taguchi are (86.1751×10-3 g/min) in copper electrode by using the parameters with (current 10 A, pulse on time 200 µs and pulse off time 25 µs) and (43.2979×10-3 g/min) in brass electrode at current 42 A, pulse on time 100 µs, and pulse off time 25 µs. The lowest EWR occurs with a value of (1.4510×10-3 g/min) with (current 10 A, pulse on time 100 µs, pulse off time 4 µs) variables when using a copper electrode. The highest WR (2.602508) was found for the brass electrode with (current 24 A, pulse on time 200 µs, pulse off time 4 µs) variables.